2016
DOI: 10.4103/0972-5229.194011
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric trauma BIG score: Predicting mortality in polytraumatized pediatric patients

Abstract: Background:Trauma is a worldwide health problem and the major cause of death and disability, particularly affecting the young population. It is important to remember that pediatric trauma care has made a significant improvement in the outcomes of these injured children.Aim of the Work:This study aimed at evaluation of pediatric trauma BIG score in comparison with New Injury Severity Score (NISS) and Pediatric Trauma Score (PTS) in Tanta University Emergency Hospital.Materials and Methods:The study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
7
2
Order By: Relevance
“…The findings of a study showed that NISS had sensitivity of 53.3% at cut-off value ≤39.5 and specificity of 54.3% for predicting mortality. 8 The observed difference in cut-off value of anatomic scoring systems between our study and other study can be due to delay in delivering the medical care to injured patients.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The findings of a study showed that NISS had sensitivity of 53.3% at cut-off value ≤39.5 and specificity of 54.3% for predicting mortality. 8 The observed difference in cut-off value of anatomic scoring systems between our study and other study can be due to delay in delivering the medical care to injured patients.…”
Section: Discussioncontrasting
confidence: 57%
“…The scoring systems can be used for timely delivering medical support and preparing the patient for surgery in early stage. 8 The most frequently used ones are general scoring systems used in both adult and pediatric patients. In our study, we evaluated the relation of ISS, NISS, RTS with mortality, hospital LOS and need for surgery in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the current study, all patients with GCS <8 at presentation were died (p<0.001). Similarly, in the study of El-Gamasy and his colleagues (17) , when comparing GCS between survivors and non-survivors, non-survivors had a significantly lower GCS. Similarly, a research by Gill et al (18) demonstrated that GCS can predict long-term health consequences following a head injury.…”
Section: Discussionmentioning
confidence: 82%
“…Self-breathing was reported in about 70% of patients. El-Gamasy et al (17) undertook a study to evaluate the accuracy of the pediatric trauma BIG score in predicting death in patients with multiple injuries, and found that only 25% of the patients had uncontrollable breathing problems.…”
Section: Discussionmentioning
confidence: 99%